Sex worker health: San Francisco style. Issue 5 (19th July 2006) - Cohan, D; Lutnick, A; Davidson, P; Cloniger, C; Herlyn, A; Breyer, J; Cobaugh, C; Wilson, D; Klausner, J
Abstract : Objectives: To describe the characteristics of sex workers accessing care at a peer based clinic in San Francisco and to evaluate predictors of sexually transmitted infections (STI). Methods: We conducted an observational study of sex workers at St James Infirmary. Individuals underwent an initial questionnaire, and we offered screening for STI at each clinic visit. We performed univariate, bivariate, and multivariable analyses to assess for predictors of STI in this population. Results: We saw 783 sex workers identifying as female (53.6%), male (23.9%), male to female transgender (16.1%), and other (6.5%). 70% had never disclosed their sex work to a medical provider. Participants represented a wide range of ethnicities, educational backgrounds, and types of sex work. The most common substance used was tobacco (45.8%). Nearly 40% reported current illicit drug use. Over half reported domestic violence, and 36.0% reported sex work related violence. Those screened had gonorrhoea (12.4%), chlamydia (6.8%), syphilis (1.8%), or herpes simplex virus 2 (34.3%). Predictors of STI included African-American race (odds ratio (OR) 3.3), male gender (OR 1.9), and sex work related violence (OR 1.9). In contrast, participants who had only ever engaged in collective sex work were less likely to have an STI (OR 0.4). Conclusions: The majority of sex workers have never discussed their work with a medical provider. Domestic violence is extremely prevalent as is work related violence. Working with other sex workers appears to be protective of STIs. STI prevention interventions should target African-American and male sex workers. Addressing violence in the workplace and encouraging sex workers to work collectively may be effective prevention strategies.